2008
DOI: 10.1007/s00415-008-0049-x
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular long-axis function in myasthenia gravis

Abstract: Myasthenia gravis (MG) primarily affects skeletal muscles, but influence on cardiac function has been suggested. The aim of this study was to assess left ventricular long-axis function in MG patients compared to healthy controls, and to examine whether any MG-related heart involvement was influenced by the acetylcholine-esterase inhibitor pyridostigmine. We found that early diastolic atrioventricular-plane velocity and tissue Doppler peak systolic strain was lower in MG patients than in controls before pyridos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Association between MG and EKG abnormalities has also been investigated in several studies [7][8][9]. It was noted that ST depression, T-wave inversion, AV and right bundle branch block, as well as atrial fibrillation, have all been described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Association between MG and EKG abnormalities has also been investigated in several studies [7][8][9]. It was noted that ST depression, T-wave inversion, AV and right bundle branch block, as well as atrial fibrillation, have all been described.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Furlund Owe et al, EKG changes in 143 patients with MG were investigated and it was discovered that there was a shorter PR interval in patients with MG versus control group (156 ms vs 170 ms, p=0.047); however, the PR interval in MG group stayed within limits of normal (120-200 ms) [9]. In our patient, initial EKG demonstrated significantly shorted PR interval (96 ms) without delta wave or pre-excitation syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies were carried out to investigate cardiac involvement in patients with MG. Some reported non-specific ECG changes, Doppler imaging, and conventional echocardiography [29]. Another study demonstrated a reduced global heart ejection fraction in 40% of MG patients without known cardiac disease after exercise interpreted as a true association between MG and heart disease [30].…”
Section: Hrmentioning
confidence: 99%
“…[13] A few studies were carried out to investigate cardiac involvement in patients with MG. Some reported nonspecific electrocardiographic (ECG) changes, Doppler imaging and conventional echocardiography, [14] while others reported variable results, which varied from asymptomatic specific ECG changes (as abnormalities of the STI, [15] dispersion of QT and T wave alternans [16] ), giant diffuse T waves, to clinically manifest abnormalities (as conduction disturbances, atrioventricular dissociation, wide QRS, [17] syncopal attacks, orthostatic hypotension, impaired heart-rate variability (HRV) [18,19] ). These significant cardiac manifestations were reported in patients with severe stages of MG and in the presence of thymoma.…”
Section: Introductionmentioning
confidence: 99%